PENDEKATAN METODE EXAMPLES NON EXAMPLES DENGAN MEDIA GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS 2 SDN 022 HARAPAN BARU INDRAGIRI HILIR - Rodiyah Rodiyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This form of research is a class action study conducted in grade 2 sdn 022 Harapan Baru Indragiri Hilir regency with 2 cycle cycleS I in the form of planning and cycle II in the form of actions using examples non examples approach with image media. The study subject consisted of 16 grade 2 students, the research instruments of observation sheets and daily replays. The purpose of the research was to improve the writing skills of grade 2 students at SDN 022 Harapan Baru. The results showed a significant improvement both in terms of teacher and student learning activities as well as students' writing skills. For the observation of teacher activity in the initial data only 55% , then after reflection of learning obtained a percentage of 85% with a good category. For the observation of student activity in the initial data obtained a percentage of 53% with a fairly good category, then after reflection of learning obtained a percentage of 92% with a good category. In the results of the student's writing ability found preliminary data with an average score of 60, then after reflection of learning obtained an average score of 88 students, based on the presentation, it can be concluded that the application of examples non examples learning methods using image media can improve the writing skills of grade 2 students at SDN 022 Harapan Baru.